Model mandat rakyat berdasarkan perilaku pengundi, daya saing politik dan sistem penyampaian politik bersepadu - Munira, Abdul Razak (2017)
The approach of political competitiveness has undergone a shift from the analysis of the general factors t that o fthe more specific. The general factors, among others include national development agenda such as economic competitiveness, economic growth, foreign investment rate and the economic market. Meanwhile, an example of a specific factorcan be lemenets associated with the election process, particularly the general elections. Therefore, this study aimed to explain the theory of political competitiveness comprising its three criteria in terms of leadership, namely candidate or individual leadership and party leadership in resolving national issues and as well as intra and inter party conflicts. The three criteria were measures using political compettiveness indicators such as competency, commitment and consistent. Descriptive statistical analysis and Network graphical estimation were used to analyse the theory. A questionnaire was developed and administered among respondents who were sampled from 13 state panels, three federal territorial panels, one political party panel from United Malays National Organisation (UMNO) and one minority group panel. A total of 745 sets of questionnaire and transcripts from 70 interview sessions were analysed using IBM Statistics Version 22.0 and Atlas.ti version 8.0 with significance findings, respectively. Results showed that from the perspective of the theory of political competitiveness and integrated political delivery system of the active cycle of the Input, Process and Ouput (IPO) quality service framework; the findings had significantly affected voters’mobility. Apparently, the application of Grounded Theory paved way to triangulate both the quantitative and qualitative data of the mixed method approach to generate the Model Mandat Rakyat (MMR). MMR provides anwers on what criteria, why and how voters analysed both candidate and party performance; in which voting as a symbolic act of giving mandate to the government and elected leaders to provide a good life for all. In conclusion, the findings of the study is in line with the definition of politics by Harold Lasswell in which politics is about the allocation of values, who gets what, when and how.